Mesenchymal Stem Cells Exposed to Persistently High Glucocorticoid Levels Develop Insulin-Resistance and Altered Lipolysis: A Promising In Vitro Model to Study Cushing’s Syndrome - Di Vincenzo, Mariangela; Martino, Marianna; Lariccia, Vincenzo; Giancola, Giulia; Licini, Caterina; Di Benedetto, Giovanni; Arnaldi, Giorgio; Orciani, Monia (Frontiers in Endocrinology, 2022)
Background: In Cushing’s syndrome (CS), chronic glucocorticoid excess (GC) and disrupted circadian rhythm lead to insulin resistance (IR), diabetes mellitus, dyslipidaemia and cardiovascular comorbidities. As undifferentiated, self-renewing progenitors of adipocytes, mesenchymal stem cells (MSCs) may display the detrimental effects of excess GC, thus revealing a promising model to study the molecular mechanisms underlying the metabolic complications of CS. Methods: MSCs isolated from the abdominal skin of healthy subjects were treated thrice daily with GCs according to two different regimens: lower, circadian-decreasing (Lower, Decreasing Exposure, LDE) versus persistently higher doses (Higher, Constant Exposure, HCE), aimed at mimicking either the physiological condition or CS, respectively. Subsequently, MSCs were stimulated with insulin and glucose thrice daily, resembling food uptake and both glucose uptake/GLUT-4 translocation and the expression of LIPE, ATGL, IL-6 and TNF-α genes were analyzed at predefined timepoints over three days. Results: LDE to GCs did not impair glucose uptake by MSCs, whereas HCE significantly decreased glucose uptake by MSCs only when prolonged. Persistent signs of IR occurred after 30 hours of HCE to GCs. Compared to LDE, MSCs experiencing HCE to GCs showed a downregulation of lipolysis-related genes in the acute period, followed by overexpression once IR was established. Conclusions: Preserving circadian GC rhythmicity is crucial to prevent the occurrence of metabolic alterations. Similar to mature adipocytes, MSCs suffer from IR and impaired lipolysis due to chronic GC excess: MSCs could represent a reliable model to track the mechanisms involved in GC-induced IR throughout cellular differentiation.